A scoping review presenting a wide variety of research on paediatric and adolescent patients with Marfan syndrome. (17th February 2020) - Lidal, Ingeborg Beate; Bathen, Trine; Johansen, Heidi; Velvin, Gry
Abstract: Aim: The present study aimed to map and summarise the research on children, aged 0‐18 years, with Marfan syndrome, identify research gaps and point to research agendas. Methods: A scoping review was systematically performed by searching multiple databases from January 1996 to April 2019. Primary studies presenting results on at least six individuals aged 0‐18 years with Marfan syndrome, diagnosed according to the Ghent nosology, were selected. Results: From 2341 de‐duplicated records, 92 papers were included, mapped and described. Their topics were diagnostics (12%), cardiovascular matters (50%), skeletal matters (22%), ocular matters (9%), other medical aspects (5%) and psychosocial perspectives (2%). Most studies were from Europe and North America and published between 1999 and 2019 in subject‐specific or paediatric journals, while a few were published in genetics journals. All studies had quantitative designs, and very few were multicentre studies. Each study had six to 608 subjects for a total of approximately 5809. Conclusion: A wide range of research topics on adolescent and paediatric Marfan syndrome was found, but qualitative studies and a focus on psychosocial matters were lacking. Future investigations addressing noncardiovascular consequences and patient experiences are needed, as well as studies reaffirming or replicating existing intervention study results.